2 - L’hétérodoxie en économie politique: de l’alternative au modèle Walrassien à la synthèse avec le néo-classicisme méthodologique: by Hakim Ben Hammouda - Hakim Ben Hammouda (Africa Development, 1996)
Drawing upon the Grenoble and Paris streams of thought, the Regulationist School (1975) analyzes the capitalist system from a historical and spatial perspective, as an alternative to the Walrassian General Equilibrium Theory. The concepts as well as the approach used are unique and contribute to an innovative analysis of both the international economic relations and the growth dynamics and crisis of the capitalist system. Criticized by conventions close to the new American institutional economy, the Regulationists are today confronted with chaotic economic phenomena and uncertainties which force them to renew their conventional tools.